Volume 3: Structures, Safety, and Reliability 2019
DOI: 10.1115/omae2019-95618
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Tests on Corroded Mooring Chains Retrieved From Various Fields in Offshore West Africa and the North Sea

Abstract: When an aged mooring system seeks a life extension, it is necessary to assess the remaining fatigue life of the corroded mooring chain. This paper summarizes the results of fatigue tests performed on mooring chain samples retrieved from six different fields in West Africa and North Sea. The impacts of corrosion on fatigue life on the samples were researched. The tests were managed under a Joint Development Project, “Fatigue of Corroded Chains (FoCCs JDP)”. The objectives of the JDP are (1) to derive a methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…4(b) shows the damage parameters on the critical plane of the Kt point are lower than those of the crown with a mean absolute difference of 0.0352 and a maximum absolute difference of 0.049, across the range of selected load amplitudes. The result is in line with full-scale experimental fatigue results [8] [9] [40], where the crown is found to be more susceptible to fatigue damage than the Kt point. This is because the Kt point has higher residual compressive stresses than at the crown upon release of the proof load.…”
Section: Calibration Of the Critical Plane Fatigue Assessmentsupporting
confidence: 88%
See 1 more Smart Citation
“…4(b) shows the damage parameters on the critical plane of the Kt point are lower than those of the crown with a mean absolute difference of 0.0352 and a maximum absolute difference of 0.049, across the range of selected load amplitudes. The result is in line with full-scale experimental fatigue results [8] [9] [40], where the crown is found to be more susceptible to fatigue damage than the Kt point. This is because the Kt point has higher residual compressive stresses than at the crown upon release of the proof load.…”
Section: Calibration Of the Critical Plane Fatigue Assessmentsupporting
confidence: 88%
“…11. The pre-tension affects the mean loads as the higher the pre-tension, the higher the mean loads, and mooring systems in the field normally have a pre-tension between 10% and 20% MBL [40], where the pre-tension in the case study is 17% MBL. As the mooring chain failures occurred in harsh sea environments [1] [3], it is hypothesised that the pre-tension of the greatest loaded line increases with the mean loads, which leads to an increase in the proportion of low-cycle fatigue causing the reported early failures in the first three years of operation.…”
Section: Discussionmentioning
confidence: 99%
“…Leira). chains have revealed that (i) the fatigue capacity of chains is strongly dependent on the mean load, and (ii) realistic corrosion pits have a detrimental effect not well represented by the simplified approach prescribed by the standards (Gabrielsen et al, 2019;Fernández et al, 2019;Zhang and Smedley, 2019;Ma et al, 2019;Lone et al, 2021). Hence, proper treatment of mean load effect and degradation due to corrosion in the calculations seems imperative to enable improved estimation of mooring line fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…Offshore mooring chains are subject to general and microbiologically influenced corrosion attacks. 17,18 During cyclic loading, corrosion pits act as stress raisers, and may become initiation sites for corrosion fatigue cracks. 18 The current work aims to improve the understanding of MSR and its influence on fatigue initiation.…”
mentioning
confidence: 99%
“…17,18 During cyclic loading, corrosion pits act as stress raisers, and may become initiation sites for corrosion fatigue cracks. 18 The current work aims to improve the understanding of MSR and its influence on fatigue initiation. Since corrosion pits vary in size and shape, 19 machined, hemispherical notches are considered here in order to develop a generic approach for MSR in R4-grade steel chains.…”
mentioning
confidence: 99%